Role of beneficial microorganisms and salicylic acid in improving rainfed agriculture and future food safety - Khan, Naeem (2020)
Fil: Khan, Naeem. University of Florida. Department of Agronom. Institute of Food and Agricultural Sciences. Gainesville, FL, USA.